What Has Changed in the Management of Uterine Serous Carcinomas? Two Decades of Experience - Michalis Liontos; Anna Svarna; Charalampos Theofanakis; Oraianthi Fiste; Angeliki Andrikopoulou; Maria Kaparelou; Konstantinos Koutsoukos; Nikolaos Thomakos; Dimitrios Haidopoulos; Alexandros Rodolakis; Meletios Athanasios Dimopoulos; Flora Zagouri (Current Oncology, 2021)
Uterine serous carcinoma accounts for 3–10% of endometrial cancers, but it is the most lethal histopathological subtype. The molecular characterization of endometrial carcinomas has allowed novel therapeutic approaches for these patients. We undertook a retrospective analysis of patients with uterine serous carcinomas treated in our hospital within the last two decades to identify possible changes in their management. The patients and their characteristics were evenly distributed across the two decades. Treatment modalities did not change significantly throughout this period. After adjuvant treatment, patients’ median disease-free survival was 42.07 months (95% CI: 20.28–63.85), and it did not differ significantly between the two decades (p = 0.059). The median overall survival was 47.51 months (95% Cl: 32.18–62.83), and it significantly favored the first decade’s patients (p = 0.024). In patients with de novo metastatic or recurrent disease, median progression-free survival was 7.8 months (95% Cl: 5.81–9.93), whereas both the median progression-free survival and the median overall survival of these patients did not show any significant improvement during the examined time period. Overall, the results of our study explore the minor changes in respect of uterine serous carcinoma’s treatment over the last two decades, which are reflected in the survival outcomes of these patients and consequently underline the critical need for therapeutic advances in the near future.